Analysis on Tourist Satisfaction with Tabek Patah Panorama Tourism Attraction in Tanah Datar Regency Based on Servqual Dimensions - Tun Huseno (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2022)
This research aims to identify the efforts conducted by the organizer of Tabek Patah Tourism in realizing tour services. In addition, the research also aims to describe the satisfaction of the tourists in general through Service Quality Dimensions which consists of tangible, reliability, responsiveness, assurance and empathy.  The method of data analysis that is used in this research is descriptive analysis by calculating the average and the median.  The data analysis technique used is calculating the level of respondent’s achievement to measure the service quality based on each service quality dimension. The results of the research find that the average of satisfaction index of Panorama Tabek Patah Visitors, based on 5 dimensions of Service Quality, is 69.76%. The highest score of respondent’s satisfaction is reliability, 72.15%. The lowest score of respondent’s satisfaction is responsiveness, 67.08%.